Analysis of Multi-physics Field Coupling Characteristics of Liquid-Immersed Shielded Motors - Li, Yifei (International Journal of Mechanical and Electrical Engineering, 2025)
This paper focuses on the special operating conditions of shielded motors in liquid environments, using a 7kW aviation pump shielded motor as a case study. A systematic analysis of its multi-physics coupling characteristics is conducted to reveal the effects of the interaction between different physical fields on the motor. First, by combining practical operating conditions, the inherent frequencies and vibration modes of the rotor system of the immersion liquid shielded motor are compared under different conditions. Then, based on the fluid field, a fluid-structure coupling analysis is performed to solve for the prestressed modal frequencies. The results show that multi-physics coupling analysis of the rotor system provides a more accurate representation of the motor’s operational characteristics compared to conventional analyses and should not be overlooked. This provides a reference for the design and optimization of such motors.